2015
DOI: 10.3923/jms.2015.105.109
|View full text |Cite
|
Sign up to set email alerts
|

Association between Walking and Cardiovascular Risk Factors in University Employees

Abstract: Walking is the simplest form of physical activity for the prevention of cardiovascular diseases. The aim of this study was to investigate the association between walking and cardiovascular risk factors in a working adult population. Walking activity was assessed using a pedometer worn over three consecutive days. Anthropometric measurements of height, weight, waist circumference, as well as blood pressure, fasting glucose and lipid concentrations were also determined. In this cross-sectional study, 112 employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
1
3
2
Order By: Relevance
“…Overall, only 6.7% of respondents followed the recommended steps for public health, that is 10,000 steps or more. This current study deviates from the study done by Abdullah et al (2015) which showed almost 17% of the respondents from 112 university employees in Kuala Lumpur achieved the recommended steps goal for public health. Several researchers have called into question the 10,000 steps a day because 10,000 walking steps are typically not practicable through normal day-to-day routines among average people (Choi et al, 2007).…”
Section: Walking Steps Assessmentcontrasting
confidence: 99%
“…Overall, only 6.7% of respondents followed the recommended steps for public health, that is 10,000 steps or more. This current study deviates from the study done by Abdullah et al (2015) which showed almost 17% of the respondents from 112 university employees in Kuala Lumpur achieved the recommended steps goal for public health. Several researchers have called into question the 10,000 steps a day because 10,000 walking steps are typically not practicable through normal day-to-day routines among average people (Choi et al, 2007).…”
Section: Walking Steps Assessmentcontrasting
confidence: 99%
“…However, the overall waist circumference and body mass index was slightly higher than normal from the normal range. This probably happened due to the majority of subjects are overweight and obese, an observation that is similar to other studies involving female populations (Poh et al, 2010;Abdullah et al, 2015). Previous studied proved that individuals who achieved 10 000 steps per day have a normal body weight whereas individuals with have a step less than 5000 steps per day are overweight or obesity (Dwyer et al, 2007;Tudor-Locke et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…The percentage of those who recorded less than 5000 steps/day was 35%. Our findings indicate that the average daily steps among our study sample was slightly higher compared with a group of university employees in Kuala Lumpur (Abdullah et al, 2015). Our study sample also recorded an average daily steps much higher compared with other studies (Tudor-Locke et al, 2004;Wyatt et al, 2005).…”
Section: Discussioncontrasting
confidence: 59%
“…This is because housekeeping, such as cleaning, cooking, and babysitting, requires a low to moderate degree of effort. Being physical active is important to reduce risk of cardiovascular disease [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%